2011
DOI: 10.1080/09298215.2011.594513
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary Restraint of Body Movement Potentially Reduces Overall SPL Without Reducing SPL Range in Western Contemporary Popular Singing

Abstract: Voluntary restriction of body movement is associated with the reduction of sound pressure level (SPL) peaks in western contemporary popular singing. This paper investigated whether overall SPL and SPL range are affected when singers voluntarily restrain their movement during performance. Six professional singers performed a section of a song in two performance modes: first with no constraints placed on their body behaviour and again when directed to stand still. Overall SPL and SPL range were compared for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Dahl & Friberg, 2007), and in violin pedagogy it is considered important that the whole body is able to move freely so that stiffness and excess muscle tension are avoided (Medoff, 1999;Roos, 2001). Furthermore, it has been shown that for singers, instructions to minimize body movement cause decreased sound pressure levels (Turner & Kenny, 2011), and in cello playing, head and torso movements contribute to the player's ability to generate fluid bowing and good quality sound (Rozé, Aramaki, Kronland-Martinet, & Ystad, 2020). These findings highlight how overall freedom of body motion might impact sound quality.…”
Section: The Whole Body In Violin Playingmentioning
confidence: 99%
See 1 more Smart Citation
“…Dahl & Friberg, 2007), and in violin pedagogy it is considered important that the whole body is able to move freely so that stiffness and excess muscle tension are avoided (Medoff, 1999;Roos, 2001). Furthermore, it has been shown that for singers, instructions to minimize body movement cause decreased sound pressure levels (Turner & Kenny, 2011), and in cello playing, head and torso movements contribute to the player's ability to generate fluid bowing and good quality sound (Rozé, Aramaki, Kronland-Martinet, & Ystad, 2020). These findings highlight how overall freedom of body motion might impact sound quality.…”
Section: The Whole Body In Violin Playingmentioning
confidence: 99%
“…The systematic changes in sway observed here, were a matter of millimetres in magnitude, suggesting changes in micro-motion rather than large swaying motions which could be disruptive to playing technique. As freedom of body motion is considered a positive pedagogical outcome (Roos, 2001), inhibiting overall body motion has been shown to negatively impact music performance (Rozé et al, 2020;Turner & Kenny, 2011), and increases in micromotion while sitting have been associated with reductions in pain (Vergara & Page, 2002), we interpreted increased instrument sway as representing subtle relaxations of posture and thus an improvement in freedom of body motion. This finding therefore supports our first hypothesis, with freer motion in proximal external relative to internal focus.…”
Section: Physical Outcomesmentioning
confidence: 99%
“…Expressive singing necessitates a variable range of pitch and intensity (loudness), in other words, vocal flexibility and strength, to contribute to the dramatic and communicative character of each performance [6]. As vocal athletes, singers may experience vocal fold inflammation and injury as a part of the demands of their career, even if healthy voice production techniques are used [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%